Successful resolution of a hemorrhagic pancreatic pseudocyst ruptured into the stomach complicating obstructive pancreatitis due to pancreatic cancer: a case report. Issue 1 (December 2016) - Hoshimoto, Sojun; Aiura, Koichi; Shito, Masaya; Kakefuda, Toshihiro; Sugiura, Hitoshi
Abstract Background Hematemesis is uncommon as an initial presenting symptom in pancreatic cancer. We present herein a case of a pseudoaneurysm that ruptured and fistulized into the stomach. The pseudoaneurysm was secondary to a pancreatic pseudocyst complicating obstructive pancreatitis due to pancreatic cancer. The patient was successfully treated using trans-arterial embolization followed by curative surgery. Case presentation A 61-year-old man presented to the emergency room with hematemesis. Laboratory examinations revealed a low level of hemoglobin (5.0 g/dl). The patient had presented to another hospital due to hematemesis 1 month before presenting to our hospital. A low-density mass in the pancreatic body with dilatation of the distal main pancreatic duct and a pseudocyst in the pancreatic tail had been observed by radiology at the previous hospital. Further investigation had been planned. Abdominal computed tomography on admission to our hospital demonstrated a pseudoaneurysm in close contact with the wall of the pseudocyst of the pancreatic tail, compressing the stomach. The pseudoaneurysm had not been detected by abdominal computed tomography at the previous hospital. Emergency selective angiography revealed that the pseudoaneurysm arose from the left gastroepiploic artery branching from the splenic artery. Trans-arterial embolization of the left gastroepiploic artery through the splenic artery was successfully performed. Elective distal pancreatectomy and splenectomy with regional lymph node dissection combined with partial resection of the stomach was performed 3 weeks after coil embolization. Pathological examination revealed a moderately differentiated tubular adenocarcinoma in the pancreatic body with regional lymph node metastasis and revealed the pseudoaneurysm rupturing into the pancreatic pseudocyst. The patient has experienced no tumor recurrence or metastasis during 1 year of follow-up. Conclusions Spontaneous rupture of a pseudoaneurysm is a rare and potentially lethal complication of a pancreatic pseudocyst. Most affected patients have a history of alcoholism and suffer from acute or chronic pancreatitis. To our knowledge, this is the first reported case of a hemorrhagic pancreatic pseudocyst complicating obstructive pancreatitis due to pancreatic cancer.